2012
DOI: 10.1038/nmeth.2021
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of true monomeric and bright photoactivatable fluorescent proteins

Abstract: Monomeric (m)Eos2 is an engineered photoactivatable fluorescent protein widely used for super-resolution microscopy. We show that mEos2 forms oligomers at high concentrations and forms aggregates when labeling membrane proteins, limiting its application as a fusion partner. We solved the crystal structure of tetrameric mEos2 and rationally designed improved versions, mEos3.1 and mEos3.2, that are truly monomeric, are brighter, mature faster and exhibit higher photon budget and label density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
421
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 462 publications
(434 citation statements)
references
References 30 publications
12
421
0
1
Order By: Relevance
“…Each mEos3.2 molecule can be turned on and off more than once before being irreversibly photobleached (32). This intrinsic blinking behavior of mEos3.2 results in each tagged molecule being localized more than once.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each mEos3.2 molecule can be turned on and off more than once before being irreversibly photobleached (32). This intrinsic blinking behavior of mEos3.2 results in each tagged molecule being localized more than once.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, each localized singlemolecule emitter contains spatial and temporal information that provides quantitative data that surpass those obtained from other super-resolution techniques. We took advantage of recent developments in instrumentation and data analysis methods (26)(27)(28)(29)(30)(31)(32) to perform FPALM super-resolution microscopy at ∼35-nm resolution (localization precision, σ loc , ∼14 nm). These methods enabled us to observe that nodes are uniform units with stoichiometric ratios and distinct distributions of constituent proteins, and provided the quantitative data necessary to build a molecular model of the node.…”
mentioning
confidence: 99%
“…We first took inspiration from the two mutations that make mEos3.2 more monomeric than mEos2: I102N and Y189A (15). Based on a sequence alignment between mEos2 and mMaple, we made the comparable mutations, I111N and Y198A, in mMaple.…”
Section: New Pafps With High Signaling Efficiency and Low Dimerizationmentioning
confidence: 99%
“…Previous studies have shown that the high accumulation of PIP2 is required for receptor protein syntaxin-1A clustering [15]. To test whether PIP2 was involved in the EGFR clustering, we labeled PIP2 in COS-7 cell membrane with a PIP2 probe consisting of the Pleckstrin homology (PH) domain [26] of phospholipase C delta fused to a photoactivatable fluorescent protein mEos3.2 [27] (PH-PLCδ-mEos3.2) and analyzed the spatial distribution of PIP2 and EGFR using PALM and dSTORM, respectively. Our data showed that PIP2, similar to EGFR protein, also formed clusters in the cell membrane (Figure 2A).…”
Section: Pip2 Depletion In the Plasma Membrane Impairs The Egfr Clustmentioning
confidence: 99%